Symbolic Interactions in Traditional Medicine Practice - Normayani, Hairun; Elsera, Marisa; Wahyuni, Sri (BELIEF: Sociology of Religion Journal, 2023)
This study aims to explain the symbolic interaction in traditional medicine of the Sungai Guntung community. The traditional treatment in question is the administration of salt acid. Giving salt acid from the patient to the shaman is still preserved and believed by the community as the key to treatment. The theory used to analyse is Herbert Blumer's Symbolic Interactionism. This research uses a qualitative method with a descriptive approach. The determination of informants was carried out by purposive sampling technique or method. Based on the results of this study, the Sungai Guntung Village community still practises traditional medicine. This research resulted in the finding that the administration of salt acid is a spiritual phenomenon where the illness comes from physical, psychological and magical sources. The meaning of tradition depends on social interaction, so the continuity of meaning is also very dependent on changes in social interaction. The symbolic interaction in this treatment is reflected in the symbol of bonding between the shaman and the patient, the symbol of the patient's trust in the shaman, the symbol of gratitude from the patient to the shaman, the symbol of the key to treatment, the symbol of the belief that illness and treatment are spiritual phenomena.